Benzothiazole Encapped Silane and Its Nano Composites for Sequential Detection of Copper Ions and Cysteine in Aqueous Solution. Issue 9 (3rd March 2021) - Singh, Gurjaspreet; Chowdhary, Kavita; Singh, Akshpreet; Satija, Pinky; Shilpy,; Diksha,; Suman,; Sushma,; Mohit,
Abstract: This work describes the study of photophysical properties of triazolelinked benzothiazole based Silane (K3) and its nanoparticles (K3‐NPs). Interestingly, both K3 and K3‐NPs exhibited highly selective chemo‐sensing ablility for Cu 2+ ions. The significance of N, S and triazole group in synthesized compounds for Cu 2+ sensing has been confirmed by structure‐property studies. Concentration dependent colorimetric metal sensing studies indicate that Cu 2+ can be detected up to 10 μM. DFT studies, colorimetric analysis, Cyclic Voltametry, absorption and emission spectroscopy techniques helped us to evaluate efficiency towards amino acids along with copper complexation. Abstract : The present article involves the study of photophysical properties of benzothiazole encapped silane and its nanoparticles. Absorption spectra, Emission spectra and Cyclic Voltammetry studies shows the use of silane and its nanocomposites as probes for the detection of copper ions and cysteine. The sensors showed selectivity and sensitivity with low value of Limit of Detection paving the way for their use as receptors for copper ions and cysteine.